2019
DOI: 10.1111/1365-2435.13406
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity or evolutionary change? An examination of the phenological response of an arctic seabird to climate change

Abstract: Phenological adjustments are an important aspect of a population's response to climate change. Changes in phenology can occur through either individual plasticity or evolutionary change within populations. Few studies have investigated both these processes in Arctic environments. Using 42 years of individual and pedigree data, we evaluated the contribution of plasticity and evolution to variation in breeding phenology at a colony of a high Arctic sea‐ice obligate seabird, Mandt's black guillemot (Cepphus gryll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The present study also provides a foundation to further develop community models with multiple activity cycles. Adaptive temporal niche shifts through phenotypic plasticity or evolution 44,45 , which can change patterns of multiple activity cycles, are a key element for the application of the present theory to a more general one.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also provides a foundation to further develop community models with multiple activity cycles. Adaptive temporal niche shifts through phenotypic plasticity or evolution 44,45 , which can change patterns of multiple activity cycles, are a key element for the application of the present theory to a more general one.…”
Section: Discussionmentioning
confidence: 99%
“…For 46 years, Divoky, of Cooper Island Arctic Research, has studied a colony of black guillemots on the island. As the planet warms, he's tracking these seabirds as they lay eggs progressively earlier (2) and their colony size and breeding success decline as a result of the loss of ice-associated prey (3). "The real long-term nature of his dataset I think is remarkable," says Coryell-Martin, who's based in Port Townsend, WA.…”
Section: Painters As Storytellersmentioning
confidence: 99%
“…In this issue of Functional Ecology , Sauve, Divoky, and Friesen () explore these issues in a high Arctic seabird, Mandt's black guillemot ( Cepphus grylle mandtii ), whose ecology is closely tied with sea ice. The Arctic is among the fastest warming regions globally, with concomitant rapid changes in spring phenology (Berteaux, Réale, McAdam, & Boutin, ).…”
mentioning
confidence: 99%
“…Using individual‐level data, Sauve et al () showed that earlier‐breeding females fledged more chicks annually and were themselves more likely to survive to the next year. This directional selection on breeding date implies population‐level maladaptation: higher mean fitness would result if the birds bred earlier, suggesting they are lagging behind an optimum.…”
mentioning
confidence: 99%
See 1 more Smart Citation